STRyper: A macOS application for microsatellite genotyping and chromatogram management - Jean Peccoud (PLoS ONE, 2025)
Microsatellite markers analyzed by capillary sequencing remain useful tools for rapid genotyping and low-cost studies. This contrasts with the lack of a free application to analyze chromatograms for microsatellite genotyping that is not restricted to human genotyping. To fill this gap, I have developed STRyper, a macOS application whose source code is published under the General Public License. STRyper only uses macOS libraries, making it very lightweight, responsive, and behaving like a modern application. Its three-pane window enables easy management and viewing of chromatograms imported from FSA and HID files, the creation of size standards and of microsatellite marker panels (including bins). STRyper features powerful search capabilities (with smart folders) and a modern graphical user interface allowing, among others, the manual correction of DNA ladders and of individual genotypes by drag-and-drop. It also introduces a new way to mitigate the effect of variations in electrophoretic conditions on estimated allele sizes.